VISUALIZATION OF MODELING PHYSICAL LAWS FOR SYSTEMS, PROCESSES AND PHENOMENA USING AUGMENTED REALITY - Kravtsov, Hennadiy; Sobol, Mykola; Tarasiuk, Artur (Journal of Information Technologies in Education (ITE), 2021)
The methods of visualization in modeling physical laws for systems, processes and phenomena using AR technologies in the educational process of secondary schools are considered. The use of augmented reality (AR) technology allows teachers to design and create effective educational resources (EER). Visual representation of the action of physical laws contributes to their better perception and understanding by students and increases their motivation to learn. A model of an educational system using augmented reality technologies was built to visualize physical laws in school textbooks. Examples of visualization of physical laws in the 8th grade physics course were considered. AR applications were developed to visualize physical laws studied in the sections "Thermal phenomena", "Electrical phenomena. Electric current". The expert method was used to assess the prospects for using augmented reality in the educational process. The result of a survey of experienced secondary school teachers in Kherson (Ukraine) confirmed the hypothesis about the effectiveness of using electronic educational resources based on AR technology. The feasibility of using such educational resources both in the classroom at school and in extracurricular work during independent learning has been confirmed. The proposed model of the learning system was tested in the classrooms of students in the process of studying in the specialties of the STEM educational paradigm.